Factors associated with decision-making on family planning use among women aged 15-49 in Guinea - Sidibe, Tiany; Camara, Sadan; Toure, Madeleine; Diallo, Aissatou; Diallo, Ramata; Sall, Alpha Oumar; Barry, Fanta; Keita, Kaba Saran; Conte, Ibrahima; Balde, Mamadou Dioulde (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: In Guinea, several factors affect women’s ability to make decisions about contraceptive use. The objective of this study was to identify factors associated with married women’s decision-making power regarding family planning use in Guinea. Methods: Data from the 2018 Guinea Demographic and Health Survey were used. A sample of 752 women was included in the study. Multivariate logistic regression was performed to determine the factors associated with women’s decision-making power regarding the use of family planning in Guinea. The Odd ratio with 95% confidence interval was calculated for the variables in the final model. Results: The overall prevalence of women deciding to use family planning was 65.47% [95%CI: 62.18 68.61]. Urban women had a 49% lower chance of deciding to use family planning than rural women (adjusted OR=0.61; 95% CI [0.238 0.92]). Similarly, women with secondary education were 3.53 times more likely to use family planning than those with no formal education (adjusted OR=3.53; 95% CI [1.27 9.78]). Conclusions: This study shows the importance of several factors in women’s decision-making power regarding family planning use in Guinea. Women with secondary education, those in the Kindia and Kankan regions, and those with a job had higher probability of deciding to use family planning. Findings from this study could help guide public health policies, emphasising the importance of education, employment and access to health services in improving women’s decision-making power when it comes to family planning in the Republic of Guinea.